Motives of reward among men who rape - Hale, Robert (American journal of criminal justice, 1997)
Perceptual deterrence research attempts to measure the effect of perceived certainty and severity of punishment in preventing criminal behavior, while considering the rewards (from the perception of the offender) of committing the crime. Many studies in the area of perceptual deterrence are lacking any measure of reward, resulting in an incomplete model. This study will examine the goals of men who commit rape to better understand what compels the rapist. Respondents for this study were drawn from the population of rapists in the maximum security state penitentiaries located in two Southern states. All were surveyed concerning the rewards that would lead them to commit rape, while considering two levels of risk of apprehension. The results reveal that those who rape often have a specific motive in mind and have calculated the risks involved in committing the offense.